Furfurylation of Pinus pinaster Wood - Esteves, B. (2009)
Furfurylation was tested with maritime pine wood (Pinus pinaster Aiton,) which is the most important pine species in Portugal. The wood was treated with a furfuryl alcohol mixture (FA 70 mix) at Kebony Products DA in Norway, in an autoclave using vacuum and pressure stages and subsequently cured and dried in a vacuum drying kiln. Both heartwood and sapwood were treated, with weight percent gains of 38% and 23% respectively. There were no significant changes on MOE and bending strength. Janka hardness increased 56% and 49%, on radial and tangential sections, respectively. Equilibrium moisture content decreased in the sapwood from 8.9 to 5.1% (at 35% relative humidity), from 12.9 to 7.3% (at 65%) and from 17.3 to 9.0% (at 85%). In heartwood the moisture decrease was very small. The dimensional stability of sapwood increased with ASE35 35.6 and 41.8%, ASE65 29.0 and 43.4% and ASE85 31.4 and 45.1% for radial and tangential directions respectively. The improvements for heartwood were smaller and only significant in the tangential direction and at the higher relative humidity values: ASE65 was 12.3 and 22.4% and ASE 85 10.5 and 24.8% for radial and tangential directions, respectively.